54.5k views
0 votes
Please answer
Find the product.
(7m^2-3m-7)(m^2-7m-6)​

User Kasimir
by
3.8k points

2 Answers

6 votes

Answer:


→(7 {m}^(2) - 3m - 7)( {m}^(2) - 7m - 6) \\ = 7 {m}^(4) - 49 {m}^(3) - 42 {m}^(2) - 3 {m}^(3) + 21 {m}^(2) + 18m - 7 {m}^(2) + 49m + 42 \\ = \boxed{ 7 {m}^(4) - 52 {m}^(3) - 28 {m}^(2) +6 7m + 42}✓

  • 7m⁴-52m³-28m²+67m+42 is the right answer.
User Pjumble
by
4.4k points
4 votes

Explanation:

(7m²-3m-7)(m²-7m-6) =

7m⁴-49m³-42m²-3m³+21m²+18m

-7m²+49m+42

= 7m⁴-52m³-28m²+67m+42

User Nfelger
by
4.5k points